Integral Representations of Mittag-Leffler Function on the Positive Real Axis - Grigoletto, E.c.; Oliveira, E.c.; Camargo, R.f. (Sociedade Brasileira de Matemática Aplicada e Computacional, 2019)
We use the method for finding inverse Laplace transform without using integration on the complex plane to show that the three-parameter Mittag-Leffler function, which appear in many problems associated with fractional calculus, has similar integral representations on the positive real axis. Some of them are presented.

Através do método para encontrar a transformada de Laplace inversa sem o uso de um contorno de integração no plano complexo, mostramos que a função de Mittag-Leffler de três parêmetros, que aparece em muitos problemas associados com cálculo fracionário, possui representações integrais similares no semieixo real positivo. Algumas delas são apresentadas.
Keywords: inverse Laplace transform; Mittag-Leffler functions; integral representations; fractional calculus; transformada de Laplace inversa; funções de Mittag-Leffler; representações integrais; cálculo fracionário